Six-Month Results of Treatment-Blinded Medication Titration for Hypertension Control Following Randomization to Endovascular Ultrasound Renal Denervation or a Sham Procedure in the RADIANCE-HTN SOLO Trial - Azizi, Michel; Schmieder, Roland; Mahfoud, Felix; Weber, Michael A.; Daemen, Joost; Lobo, Melvin D.; Sharp, Andrew S. P.; Bloch, Michael J.; Basile, Jan; Wang, Yale; Saxena, Manish; Lurz, Philipp; et al. (Circulation, 2019)
BACKGROUND: The multicenter, international, randomized, blinded, sham-controlled RADIANCE-HTN SOLO trial demonstrated a 6.3 mmHg greater reduction in daytime ambulatory systolic blood pressure (BP) at 2 months by endovascular ultrasound renal denervation (RDN) compared with a sham procedure among patients not treated with antihypertensive medications. We report 6-month results following the addition of a recommended standardized stepped-care antihypertensive treatment (SSAHT) to the randomized endovascular procedure under continued blinding to initial treatment. METHODS: Patients with a daytime ambulatory BP greater ≥135/85 mmHg and <170/105 mmHg after a 4-week discontinuation of up to 2 antihypertensive medications and a suitable renal artery anatomy, were randomized to RDN (n=74) or sham (n=72). Patients were to remain off antihypertensive medications throughout the first 2 months of follow-up unless safety BP criteria were exceeded. Between 2 and 5 months, if monthly measured home BP was ≥135/85 mmHg, a SSAHT was recommended consisting of the sequential addition of amlodipine 5 mg/day, a standard dose of an angiotensin converting enzyme inhibitor/angiotensin receptor blocker, and hydrochlorothiazide 12.5 mg/day, followed by the sequential uptitration of hydrochlorothiazide (25 mg/day) and amlodipine (10 mg/day). Outcomes included the 6-month (i) change in daytime ambulatory systolic BP adjusted for medications and baseline SBP, (ii) medication burden, and (iii) safety. RESULTS: A total of 69/74 RDN patients and 71/72 sham patients completed the 6-month ambulatory BP measurement. At 6 months, 65.2% of patients in the RDN group were treated with the SSAHT vs. 84.5% in the sham group (p=0.008) and the average number of antihypertensive medications and defined daily dose were less in the RDN group than in the sham group (0.9±0.9 vs. 1.3±0.9, p=0.010 and 1.4±1.5 vs. 2.0±1.8, p=0.018; respectively). Despite less intensive SSAHT, RDN reduced daytime ambulatory systolic BP to a greater extent than sham (-18.1±12.2 vs. -15.6±13.2 mmHg, respectively; difference adjusted for baseline BP and number of medications: -4.3 mmHg, 95% confidence interval, -7.9 to -0.6, p=0.024). There were no major adverse events in either group through 6 months. CONCLUSIONS: The BP lowering effect of endovascular ultrasound RDN was maintained at 6 months with less prescribed antihypertensive medications compared with a sham control. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02649426.
EVALuna2:118642